Explosion induced rogue waves and chaotic multi-pulsing in a passively mode-locked all-normal dispersion fiber laser. (27th May 2020) - Das Chowdhury, Sourav; Dutta Gupta, Bhaswar; Chatterjee, Sayan; Sen, Ranjan; Pal, Mrinmay
Abstract: In this work, an experimental study of non-stationary pulse dynamics consisting of explosion events and chaotic multi-pulsing from an all-normal dispersion Yb-fiber laser operating in noise-like pulse (NLP) state have been reported. During explosion in NLP state, which resembled soliton explosion, dispersive Fourier transform measurements revealed large, intermittent amplitude fluctuations in the real-time spectrum indicative of rogue waves. The fluctuations either appeared randomly at the lasing wavelength within the Yb-gain spectra or at the frequency downshifted Raman Stokes wavelength. It was also observed that such fluctuation at the Raman wavelength could even exceed the amplitude of the spectral components at the main lasing wavelength. With suitable adjustments to polarization controllers, the laser operation could be switched to chaotic multi-pulsing state where the acquisition of a large number of consecutive roundtrips revealed inter-pulse motion with unique trajectories occurring over millisecond time scales.